Development of hardware architecture applied to real-Time monitoring in drinking water distribution system of the Loja city [Desarrollo de la arquitectura hardware aplicada al monitoreo en tiempo real del Sistema de Distribución de Agua Potable de la ciudad de Loja] - Calderon Cordova, C. (2016)
As the population increases, it also increases the demand for water resources; this implies a challenge for the professionals that work in activities related to water supply systems, because these systems must ensure the availability and proper water quality. In Ecuador, the Municipalities are the responsible of the operation and maintenance of the drinking water distribution systems (DWDS), nevertheless some Municipalities do not have strategies and tools for water management, this management will increase index of availability and quality of service; one of the components of the water management is the variables monitoring subsystem. Furthermore, according to experts in DWDS, pressure and flow variables are the most relevant for the calculation of performance indicators proposed by the IWA (International Water Association), the OFWAT (Water Services Regulation Authority) and by the ISO 24512 standard (Drinking Water Management). This project proposes the development of hardware architecture of a portable remote monitoring node applied to hydraulic variables pressure and flow in the DWDS; the developed prototype was evaluated in a water node at UTPL campus and also in a water underground node in the DWDS of the Loja city.